And the beat goes on. The continued trials and tribulations of passenger rail franchising in Great Britain. (November 2020) - Preston, John; Bickel, Charles
Abstract: National rail passenger services in Great Britain have been largely delivered by a system of franchising since 1996. As reported at previous Thredbo Conferences, this system has had several iterations and a number of failures, with one franchise (for the East Coast) having failed three times. This paper will use national level and operator specific data provided by the Office of Rail and Road (ORR) to review recent key trends in rail demand and supply. It will extend an existing modelling framework to determine the costs and benefits of rail franchising at the national level. It will also undertake case studies of two franchises, for the East Coast and South West. In advance of the on-going Williams Review, policy prescriptions will be suggested for both the commercial and the social railway with particular reference to contract specifications.